The Effectiveness of Health Education Using Web-Based Family Planning Information Media "Life Care" in Improving Acceptors' Knowledge - Roza Asnel; Salsabila Oktoviani; Tengku Hartian SN; Mailiza Cahyani; Dewinny Septalia Dale (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
One approach to strengthening the quality of human resources is to ensure that individuals have access to reliable reproductive health information, particularly by improving knowledge about contraception through innovative digital platforms. This study examined the effectiveness of digital health education delivered through the “LIFE CARE” platform in enhancing reproductive health knowledge related to contraceptive methods among current contraceptive users. The observation was carried out at the Karya Wanita Community Health Centre in Pekanbaru City from January to July 2024, involving 77 participants selected purposively from a total of 220 contraceptive users. A one-group pretest-posttest design was applied, and knowledge scores were analyzed using the Wilcoxon test with SPSS version 25 software. Results demonstrated a significant increase in knowledge after the intervention, with median scores rising from 75 (SD = 14.27) before the intervention to 95 (SD = 6.10) post-intervention (p < 0.001). These findings confirm that web-based educational interventions are effective in enhancing contraceptive knowledge and highlight their potential to strengthen family planning services and digital health education strategies at the primary healthcare level. Keywords: Digital Health Promotion, Web-Based Education, Family Planning, Contraceptive Knowledge, Reproductive Health